2019
DOI: 10.1016/j.jcp.2018.11.009
|View full text |Cite
|
Sign up to set email alerts
|

A p-multigrid strategy with anisotropic p-adaptation based on truncation errors for high-order discontinuous Galerkin methods

Abstract: High-order discontinuous Galerkin methods have become a popular technique in computational fluid dynamics because their accuracy increases spectrally in smooth solutions with the order of the approximation. However, their main drawback is that increasing the order also increases the computational cost. Several techniques have been introduced in the past to reduce this cost. On the one hand, local mesh adaptation strategies based on error estimation have been proposed to reduce the number of degrees of freedom … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 70 publications
0
30
0
Order By: Relevance
“…It has been shown that the use of FAS p-multigrid methods speeds up the computation of steady-state and unsteady solutions of the compressible Navier-Stokes equations [2,8]. In addition, Rueda-Ramírez et al [18] showed that the truncation error of an anisotropic representation can be inexpensively obtained inside an anisotropic p-multigrid cycle that performs the coarsening in one coordinate direction at a time. In fact, the second term of Eq.…”
Section: The P-adaptation Multigrid Schemementioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that the use of FAS p-multigrid methods speeds up the computation of steady-state and unsteady solutions of the compressible Navier-Stokes equations [2,8]. In addition, Rueda-Ramírez et al [18] showed that the truncation error of an anisotropic representation can be inexpensively obtained inside an anisotropic p-multigrid cycle that performs the coarsening in one coordinate direction at a time. In fact, the second term of Eq.…”
Section: The P-adaptation Multigrid Schemementioning
confidence: 99%
“…In this work, we focus on truncation error estimates since it has been shown that a reduction of the truncation error controls the numerical accuracy of all functionals [10], hence reducing the truncation error necessarily leads to a more accurate lift and drag. The τ -estimation method [4] is a way to estimate the truncation error locally that has been used to drive mesh adaptation strategies in low-order [9,20] and high-order methods [10,17,18]. The adaptation strategy consists in converging a high order representation (reference mesh) to a specified global residual and then performing a single error estimation followed by a corresponding mesh adaptation process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This simple test case serves to illustrate the potential of the elementwise SGWT as an error indicator for carrying out h ‐adaptivity within the framework of a DG‐FEM discretization and constitutes an interesting prospect for future research. A similar application of this procedure to a laminar incompressible test case has been demonstrated by Pinto et al We must point out that p ‐adaptivity is also well suited to be applied within the DG‐FEM framework, as indicated by several recent works . It is highly likely that the elementwise SGWT error indicator presented above may be appropriate for use within this setting as well.…”
Section: Numerical Setupmentioning
confidence: 99%
“…A similar application of this procedure to a laminar incompressible test case has been demonstrated by Pinto et al 82 We must point out that p-adaptivity is also well suited to be applied within the DG-FEM framework, as indicated by several recent works. [83][84][85] It is highly likely that the elementwise SGWT error indicator presented above may be appropriate for use within this setting as well.…”
Section: Figure 11mentioning
confidence: 99%